1984
DOI: 10.1159/000284093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trazodone in the Treatment of Depressed Cardiac Patients

Abstract: The novel antidepressant trazodone is hypothesized to be less cardiotoxic than the tri-tetracyclic antidepressants. Recently, however, 2 patients with preexisting ventricular irritability showed an increased number of ventricular premature beats and of repetitive forms after starting on trazodone. Data are presented here from four studies on the cardiovascular safety of trazodone. Conclusions are: (1) Trazodone has little effect on cardiac conduction. (2) Trazodone does not worsen supraventricular arrhythmias.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Further study of ventricular irritability has yielded little in the way of conclusive evidence that there is any major risk that trazodone will exacerbate ventricular conduction problems [19]. Other cardiac side effects have also been reported [20], Overall, however, stud ies over the past 5 years have tended to demonstrate relatively minor nonspecific effects of trazodone on cardiac function in both healthy subjects and cardiac patients [3,4,8,19]. Nonetheless, as with any drug, patients with major arrhythmias or signifi cant underlying heart disease should be fol lowed closely.…”
Section: Discussionmentioning
confidence: 99%
“…Further study of ventricular irritability has yielded little in the way of conclusive evidence that there is any major risk that trazodone will exacerbate ventricular conduction problems [19]. Other cardiac side effects have also been reported [20], Overall, however, stud ies over the past 5 years have tended to demonstrate relatively minor nonspecific effects of trazodone on cardiac function in both healthy subjects and cardiac patients [3,4,8,19]. Nonetheless, as with any drug, patients with major arrhythmias or signifi cant underlying heart disease should be fol lowed closely.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only when trazodone was used in patients with preexisting cardiac disease did reports ap pear that suggest that trazodone therapy may cause a different and potentially dangerous form of toxicity -ventricular arrhythmias [7][8][9]. Although it is not yet clear that trazo done is actually arrhythmogcnic, these stud ies suggest that trazodone may pose a prob lem and, therefore, should not be used in depressed patients with preexisting ventricu lar arrhythmia.…”
Section: Trazodone's Cardiovascular Safety Profilementioning
confidence: 99%
“…However, trazodone is not a perfect drug; it can cause orthostatic hypotension and has been impli cated in causing ventricular arrhythmias [7][8][9], It is currently unclear whether trazodone causes ventricular arrhythmias; thus, it would not be the drug of choice in a de pressed patient with concomitant ventricu lar arrhythmia. This article will review the TCA drugrelated cardiovascular side effects in patients with normal hearts and in those patients with cardiac disease.…”
mentioning
confidence: 99%
“…Himmelhoch et al [33] reviewed the car diovascular literature and concluded that trazodone therapy had little effect on cardiac conduction, did not worsen supraventricular arrhythmias, and produced fewer incidents of postural hypotension than most other an tidepressants. Additionally, he suggested that lower doses of trazodone (100-300 mg) were better tolerated and more effective in major depressive patients simultaneously suffering significant cardiovascular disease.…”
Section: Safety Profilementioning
confidence: 99%